Perceptual-motor performance and neural conduction asymmetries in elite basketball players - Devrilmez, M.; Soslu, R.; Devrilmez, E.; Uysal, A.; Özer, Ö.; Akgül, M. S.; Thapa, R. K.; Çuvalcioglu, I. C.; Uysal, H. S. (BMC Sports Science, Medicine and Rehabilitation, 2026)
Background This study investigated whether the dominant hand would exhibit faster nerve conduction velocity, lower muscle activation latency, and superior Coincidence Anticipation Timing (CAT) performance compared to the non-dominant hand, reflecting enhanced neuromuscular efficiency and perceptual accuracy due to sport-specific training adaptations.